Аналіз забезпечення захисту інформації в мережах 5G з технологією MASSIVE MIMO - Поповська, Є. О.; Марчук, В. С. (ХНУРЕ, 2023)
Advanced MIMO technology - massive MIMO is implemented in modern 5G wireless telecommunication systems. Base stations use antenna arrays with hundreds or even thousands of elements. Multi-beam antenna arrays make it possible to increase the bandwidth and spectral efficiency of the communication system. Each of the rays of the directional diagram serves its own group of users. This technology is usually implemented in the range of millimeter radio waves. The use of this range makes it possible to design antenna arrays of rather small sizes with a large number of antenna elements. 5G networks have many advantages over the previous generation of 4G. But at the same time, such networks have a number of security problems. The paper analyzes the main security problems of 5G networks with massive MIMO technology and ways to reduce them.
Keywords: технологія MASSIVE MIMO; мережа 5G